Kapasitas Kelembagaan Kelompok Petani dalam Pengembangan Usaha Kopi Hulu Hilir di Kabupaten Jember: Politeknik Negeri Jember - Sundari, Sri; Agustinus Waluyo, Donny; Kustiari, Tanti; Ahsin Kusuma Mawardi, Ahmad (Politeknik Negeri Jember, 2025)
Jember as one of the largest coffee producers in East Java does not seem to be able to prosper its Jember as one of the largest coffee producers in East Java has not been able to prosper its farmers. This was due to the low level of institutional capacity of farmer groups to carry out their functions and roles in increasing the capacity of farmers in developing upstream and downstream coffee businesses in Jember Regency. This study aims was to describe and analyze the influence of motivation, training activities and group functions both directly and indirectly on the institutional capacity of coffee farmers. The results showed that (1) the motivation of coffee farmers has not reached the good category because the training activities and the materials have not been maximized absorbed by coffee farmers. So, the function of farmer groups has not run well, and the institutional capacity of farmer groups in the development of upstream and downstream coffee businesses in Jember Regency was not high, (2) Motivation does not have a direct significant and also indirect effect on institutional capacity through a group functions was not good. Meanwhile, training activities have a direct or indirect effect on institutional capacity through group functions that was significantly good. The greatest influence on training activities depended on group functioning of coffee business